Transhumant Sheep Grazing Enhances Ecosystem Multifunctionality in Productive Mountain Grasslands: A Case Study in the Cantabrian Mountains - Fernández-Guisuraga, José Manuel; Fernández-García, Víctor; Tárrega, Reyes; Marcos, Elena; Valbuena, Luz; Pinto, Rayo; Monte, Paula; Beltrán, David; Huerta, Sara; Calvo, Leonor (Frontiers in Ecology and Evolution, 2022)
Understanding the effects of traditional livestock grazing abandonment on the ability of mountain grasslands to sustain multiple ecosystem functions (ecosystem multifunctionality; EMF) is crucial for implementing policies that promote grasslands conservation and the delivery of multiple ecosystem services. In this study, we evaluated the effect of short- and long-term transhumant sheep abandonment on EMF through a grazing exclusion experiment in a grassland of the Cantabrian Mountains range (NW Spain), where transhumant sheep flocks graze in summer. We considered four key ecosystem functions, derived from vegetation and soil functional indicators measured in the field: (A) biodiversity function, evaluated from total plant species evenness, diversity and richness indicators; (B) forage production function, evaluated from cover and richness of perennial and annual herbaceous species indicators; (C) carbon sequestration function, evaluated from woody species cover and soil organic carbon indicators; and (D) soil fertility function, evaluated from NH4+-N, NO3–N, P and K content in the soil. The EMF index was calculated by integrating the four standardized ecosystem functions through an averaging approach. Based on linear mixed modeling we found that grazing exclusion induced significant shifts in the considered individual ecosystem functions and also on EMF. Long-term livestock exclusion significantly hindered biodiversity and forage production functions, but enhanced the carbon sequestration function. Conversely, the soil fertility function was negatively affected by both short- and long-term grazing exclusion. Altogether, grazing exclusion significantly decreased overall EMF, especially in long-term livestock exclusion areas, while the decline in EMF in short-term exclusions with respect to grazed areas was marginally significant. The results of this study support the sustainability of traditional transhumance livestock grazing for promoting the conservation of grasslands and their ecosystem function in mountain regions.